Analysis of the Use of Surplus and ISAK 35 in Non-Profit Financial Statements: Evidence from NU Insan Cendikia Kediri - Nadhifa, Tsania Qotrunnada; Abdani, Fadlil (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2023)
The aim of this research is to evaluate the application of ISAK 35 in preparing financial reports for non-profit entities and the Regulation of the Minister of Finance of the Republic of Indonesia number 68/pmk. 03/2020 in using excess balance in non-profit entities. The background to this research is the incompatibility between the Foundation's financial reports and ISAK 35 and the absence of administration regarding reporting on the use of surplus at the Foundation. This is due to the lack of knowledge of the applicable financial regulations by the parties who regulate the Foundation's finances. The type of research used in this research is case study research. So, the results and conclusions of this research only apply to the NU Insan Cendikia Education Foundation, Kediri City. The results of this research show that the NU Insan Cendikia Education Foundation in Kediri City in preparing financial reports is still simple, then it has been adjusted by the researcher to the applicable regulations, namely ISAK 35. In using the surplus of the NU Education Foundation, Insan Cendikia has implemented the applicable regulations, namely Regulation of the Minister of Finance of the Republic of Indonesia number 68/pmk. 03/2020 by using it again to procure its own infrastructure in the first and second years after the remaining balance has been used, but the Foundation has not carried out administration.